Introduction to the Theoretical Framework of Dunning’s Investment Development Path - Nguyen, Thi Kim Anh (H. : ĐHQGHN, 2017)
Proposed in 1981 by John H. Dunning, the investment development path (known as the IDP model) has been considered to be an application of the eclectic paradigm. It is an expansion of Dunning’s terms on internationalizing activities of TNCs at a macro level in order to explain a country’s FDI patterns. The nature of the IDP model is a dynamic approach which examines the systematic relationship between a country’s net position of foreign direct investment (both inward and outward FDI) and its different stages of development. Recently, numerous authors around the world have conducted research about the development of investment using the IDP model for countries and/or groups of countries that have been effective in terms of policy implications. This article briefly collects and introduces some theoretical aspects of Dunning’s IDP model aiming at providing a theoretical framework for further research on FDI